The Effect of Job Stress on Organizational Citizenship Behavior With Job Satisfaction as a Mediating and Tenure as a Moderating - Daniyatul Farhiya; Noermijati Noermijati; Nur Prima Waluyowati (Journal of Business and Management Review, 2023)
This study aims to determine the role of job stress and job satisfaction in influencing Organizational Citizenship Behavior, as well as the role of job satisfaction as a mediating variable and tenure as a moderating variable in PT X employees. Data collection methods using questionnaires, and saturated sample respondents, namely 135 employees of PT X. The data analysis technique makes use of the SmartPLS 3.3 software program and the partial least square (PLS) approach, which is based on structural equation modeling (SEM). The findings demonstrated that job stress has a significant negative impact on OCB, job stress has a significant negative impact on job satisfaction, job satisfaction has a significant positive impact on OCB, job satisfaction can partially mediate between job stress and OCB, and tenure can moderate, thereby weakening the effect of job satisfaction on OCB, and that the lower the tenure associated with the longer employee tenure, the lower the OCB behavior in employees. This is because employees with longer tenure, the more they decrease to behave extra roles in the organization.